Incidence of Periodontal Pocket Development in Distal Root of Mandibular Second Molar Following Impacted Third Molar Removal in Compare to Using Bone Graft & Platelet rich Plasma - Salim Jaafer, Samer; Mohammed Aldaghir, Osamah; Saad Hanfoosh, Hayder; Abbass Hamad, Fadhil (International Journal of Psychosocial Rehabilitation, 2020)
Background : Extraction of a deep impacted mandibular third molar leads to a periodontal defect in the adjacent second molar; the use of bone graft & PRP as regenerative material aids in healing improvement & preventing periodontal pocket development. Materials and Methods: The population sample included in this research was randomly selected from patients attending the teaching dental hospital of the college of dentistry/Almuthana University seeking dental treatment. 30 patients (20 females & 10 males); the age of these patients ranged from 17 to 26 years. All selected patients were nonsmokers, with bilateral mandibular third molar inclusion in mesio-horizontal position. In the study group, the alveolar cavity was filled with PRP and BPBM alone. The alveolar cavities of the control group were treated without PRP & BPBM. Inclusion criteria included the presence of a pocket that was located distally to the second mandibular molar with a probing depth greater than or equal to 7mm. Results: Following 18 weeks, a significant reduction in pocket depth & gain in clinical attachment level at the distal root of the second molar in both groups treated with bone graft & platelet-rich plasma compared to the control group. Conclusion: The use of bone graft & platelet-rich plasma is necessary for filling bony defects following deep impacted third molar extraction to prevent periodontal defect development distally to the second molar and improve new bone regeneration.